Climate change what everyone needs to know - Joseph Romm (New York, NY Oxford University Press, 2018)
he essential primer on what will be the defining issue of our time, Climate Change: What Everyone Needs to Knowʼ is a clear-eyed overview of the science, conflicts, and implications of our warming planet.
Includes bibliographical references and index.
Keywords: Climatic changes--Health aspects